If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 51 + -1y(3y + 4) = 2(17 + -2y) + -58 Reorder the terms: 51 + -1y(4 + 3y) = 2(17 + -2y) + -58 51 + (4 * -1y + 3y * -1y) = 2(17 + -2y) + -58 51 + (-4y + -3y2) = 2(17 + -2y) + -58 51 + -4y + -3y2 = (17 * 2 + -2y * 2) + -58 51 + -4y + -3y2 = (34 + -4y) + -58 Reorder the terms: 51 + -4y + -3y2 = 34 + -58 + -4y Combine like terms: 34 + -58 = -24 51 + -4y + -3y2 = -24 + -4y Add '4y' to each side of the equation. 51 + -4y + 4y + -3y2 = -24 + -4y + 4y Combine like terms: -4y + 4y = 0 51 + 0 + -3y2 = -24 + -4y + 4y 51 + -3y2 = -24 + -4y + 4y Combine like terms: -4y + 4y = 0 51 + -3y2 = -24 + 0 51 + -3y2 = -24 Solving 51 + -3y2 = -24 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-51' to each side of the equation. 51 + -51 + -3y2 = -24 + -51 Combine like terms: 51 + -51 = 0 0 + -3y2 = -24 + -51 -3y2 = -24 + -51 Combine like terms: -24 + -51 = -75 -3y2 = -75 Divide each side by '-3'. y2 = 25 Simplifying y2 = 25 Take the square root of each side: y = {-5, 5}
| 16-3x=5(x+3) | | u=(m+n)x | | (3x-1)(4x+5)=(4x+5)(2x-1) | | y-4x+3=17 | | 6x^2-14x-12=0 | | 7(x-2)+5x=6(2x+5)-10 | | 3(4x-2)=28 | | (8+2x)(12+2x)=96 | | 1.50(203-y)+2.50y=372.50 | | 4x^2+40x=0 | | 2x-6=2x+11 | | 3a^2-12=0 | | 5t-8=16-t | | x+2x(x+10)=12-5x | | 9(a-14)+2(a+41)=a+1 | | 4x+2+7x-14=1-9(x+1) | | (x+30)=3 | | 7(a-4)+2(a+12)=a-8 | | y=18z | | 7x^2=7-8x | | -7x-2=8x+13 | | 80=2(x+2)+2(4x-10) | | 12-2p=q | | 3=x+x+x | | 4x-(3x+8)=5 | | 1.6x=.7x | | 19-4e+7e=106 | | 4x-4=-32 | | 4X^2+4X+13=0 | | -18=-7y+3(y+2) | | 6(5x-8)-20=11(2x-3)+3x | | 2n^2+4n+1=0 |